Engaging dropouts with differentiated practices: some evidence from Chile. Issue 6 (2nd November 2021) - Espinoza, Oscar; González, Luis Eduardo; McGinn, Noel; Castillo, Dante
ABSTRACT: The objective of this study was to identify those activities that re-engage out-of-school youth who enrol in the so-called 'recovery' schools now operating in Chile. Recovery schools can offer different kinds of activities in order to engage their students; are some activities more effective than others? Is their effect moderated by the type of dropouts who participate? Chile recently opened a national programme of Second Opportunity Schools (Escuelas de Segunda Oportunidad). Their mission is to provide primary and high school dropouts between 14 and 18 years of age an opportunity to complete their studies. Latent Class analysis, based on conventional demographic and current activity data, was used to classify these students into four distinct groups. The groups varied in their level of satisfaction (or engagement) with the Second Opportunity School in which they were studying. Within each School, the groups' satisfaction varied according to the activities in which students participated. That is, variation in satisfaction was more a result of student characteristics than differences between Schools. Some activities were more effective than others in engaging or satisfying some types of students. Further research is required to assess the impact of more highly differentiated programmes with more activities.